Knowledge emergence : (Oxford University Press, 2001)
This book brings together the research of a number of scholars in the field of knowledge creation and imparts a sense of order to the field. The chapters share three characteristics: they are all grounded in extensive qualitative and/or quantitative research; they all go beyond the meredescription of the knowledge-creation process and offer both theoretical and strategic implications; they share a view of knowledge creation and knowledge transfer as delicate processes, necessitating particular forms of support from managers